CONSTRAINTS FACED BY FISH FARMERS IN ANAMBRA STATE, NIGERIA - OHATURUONYE , SAMPSON.O; OKEKE, P.A; UKAGWU, JOHN (Nigerian Journal of Fisheries, 2022)
The major constraints faced by aquaculturists operating within Anambra State, Nigeria were investigated between the month of January, 2021 to December 2021 with a view of proffering solutions to them. A sample of 80 fish farmers were selected within the four agricultural zones of Anambra using Taro Yamani formula. Field observation, oral interviews, questionnaires and visits to farm sites were used to access the farmers. The result on socioeconomic characters of the farmers revealed that there were more male fish farmers (75.8%), average fish farmers age ranged from 41—50 years (34.7%), with majority of them being married (71.3%). They were also educated with primary education (48.8 %) and an average household number of 4 – 6 persons (60.0%). Overall mean for production constraints were (3.32), environmental constraints (3.17), socio-cultural (3.06) institutional constraints (3.40), infrastructural, financial, technological and marketing constraints were (3.72, 3.72, 3.51, and 3.32 ) respectively, and they all were above 2.5 likert scale indicating they were all major constraints. Infrastructural and financial constraints were identified as the most major constraints among all of them and ranked highest with mean range of 3.72 both among the other constraints. In conclusion, government of Anambra state is advised through the findings of this study to as a matter of urgency embark upon massive infrastructural development to stem the tide of rural- urban migration among the youths in the state as well as supporting these fish farmers with soft loans, grants, and other financial assistance in order to solve some of these identified constraints.